Developing and evaluating health education learning package (HELP) to control soil-transmitted helminth infections among Orang Asli children in Malaysia - Al-Delaimy, A.K.; Al-Mekhlafi, H.M.; Lim, Yvonne Ai Lian; Nasr, N.A.; Sady, H.; Atroosh, W.M.; Mahmud, Rohela (BMC, 2014)
Background: This study was carried out to develop a health education learning package (HELP) about soil-transmitted helminth (STH) infections, and to evaluate what impact such a package could have in terms of reducing the incidence and intensity of STH infections among Orang Asli schoolchildren in Pahang, Malaysia.